Strategies to Identify Mesenchymal Stromal Cells in Minimally Manipulated Human Bone Marrow Aspirate Concentrate Lack Consensus. Issue 5 (April 2021) - Ruoss, Severin; Walker, J. Todd; Nasamran, Chanond A.; Fisch, Kathleen M.; Paez, Conner J.; Parekh, Jesal N.; Ball, Scott T.; Chen, Jeffrey L.; Ahmed, Sonya S.; Ward, Samuel R.
Background: There is a need to identify and quantify mesenchymal stromal cells (MSCs) in human bone marrow aspirate concentrate (BMAC) source tissues, but current methods to do so were established in cultured cell populations. Given that surface marker and gene expression change in cultured cells, it is doubtful that these strategies are valid to quantify MSCs in fresh BMAC. Purpose: To establish the presence, quantity, and heterogeneity of BMAC-derived MSCs in minimally manipulated BMAC using currently available strategies. Study Design: Descriptive laboratory study. Methods: Five published strategies to identify MSCs were compared for suitability and efficiency to quantify clinical-grade BMAC-MSCs and cultured MSCs at the single cell transcriptome level on BMAC samples being used clinically from 15 orthopaedic patients and on 1 cultured MSC sample. Strategies included (1) the guidelines by the International Society for Cellular Therapy (ISCT), (2) CD271 expression, (3) the Ghazanfari et al transcriptional profile, (4) the Jia et al transcriptional profile, and (5) the Silva et al transcriptional profile. Results: ISCT guidelines did not identify any MSCs in BMAC at the transcriptional level and only 1 in 9 million cells at the protein level. Of 12, 850 BMAC cells, 9 expressed the CD271 gene. Only 116 of 396 Ghazanfari genes were detected in BMAC, whereas no cells expressed all of them. No cells expressed all Jia genes, but 25 cells expressed at least 13 of 22. No cells expressed all Silva genes, but 19 cells expressed at least 8 of 23. Most importantly, the liberalized strategies tended to identify different cells and most of them clustered with immune cells. Conclusion: Currently available methods need to be liberalized to identify any MSCs in fresh human BMAC and lack consensus at the single cell transcriptome and protein expression levels. These different cells should be isolated and challenged to establish phenotypic differences. Clinical Relevance: This study demonstrated that improved strategies to quantify MSC concentrations in BMAC for clinical applications are urgently needed. Until then, injected minimally manipulated MSC doses should be reported as rough estimates or as unknown.